2017
DOI: 10.1093/nar/gkx1071
|View full text |Cite
|
Sign up to set email alerts
|

MobiDB 3.0: more annotations for intrinsic disorder, conformational diversity and interactions in proteins

Abstract: The MobiDB (URL: mobidb.bio.unipd.it) database of protein disorder and mobility annotations has been significantly updated and upgraded since its last major renewal in 2014. Several curated datasets for intrinsic disorder and folding upon binding have been integrated from specialized databases. The indirect evidence has also been expanded to better capture information available in the PDB, such as high temperature residues in X-ray structures and overall conformational diversity. Novel nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 202 publications
(172 citation statements)
references
References 62 publications
2
164
0
Order By: Relevance
“…For example, MSH4 exhibits evidence for adaptive evolution along the mammalian phylogeny and shows an excess of nonsynonymous polymorphisms within humans. These two seemingly disparate results are unified by the observation that all six codons in MSH4 with significant signatures of positive selection (BEB, P > 0.95) are highly localized in the first 100-bp of the gene, in a putative DNA binding domain (Rakshambikai et al 2013;Piovesan et al 2017).…”
Section: Discussionmentioning
confidence: 94%
“…For example, MSH4 exhibits evidence for adaptive evolution along the mammalian phylogeny and shows an excess of nonsynonymous polymorphisms within humans. These two seemingly disparate results are unified by the observation that all six codons in MSH4 with significant signatures of positive selection (BEB, P > 0.95) are highly localized in the first 100-bp of the gene, in a putative DNA binding domain (Rakshambikai et al 2013;Piovesan et al 2017).…”
Section: Discussionmentioning
confidence: 94%
“…complexity and a low probability to form stable secondary structures. Furthermore, HVR-2 and HVR-3 were consistently predicted to be intrinsically disordered by the disorder prediction algorithms Pondr-FIT, Pondr VL-XT (Bomma et al, 2012), DISOPRED3 (Jones and Cozzetto, 2014), MobiDB 3.0 (Piovesan et al, 2017) and metaPrDOS (Ishida and Kinoshita, 2008) (Table 2; Fig. 3).…”
Section: Mapping Phosphorylation Sites To Functional Domains Of Nsp2-mentioning
confidence: 88%
“…Sequence analysis and protein structure prediction: Multiple sequence alignments were performed using the built-in ClustalW program of CLC Main Workbench 8.1 (CLC bio, Aarhus, Denmark). Intrinsic disorder prediction was conducted using multiple online programs including Pondr-FIT (Xue et al, 2010), Pondr VL-XT (Bomma et al, 2012), DISOPRED3 (Jones and Cozzetto, 2014), MobiDB 3.0 (Piovesan et al, 2017), and metaPrDOS (Ishida and Kinoshita, 2008). Protein secondary structure profiles and tertiary structure predictions were generated by homology modeling using I-TASSER (Yang et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Second, we investigated whether the distributions of UNEECON scores varied across different types of protein regions annotated by UniProt [47,48] and Mo-biDB [49]. We observed that the distributions of UNEECON scores were similar among α-helices, β-strands, and hydrogen-bonded turns (Fig.…”
Section: Uneecon Scores Capture Variation Of Negative Selection Withimentioning
confidence: 99%
“…Therefore, missense mutations in intrinsically disordered proteins may be under weak negative selection even if loss-of-function mutations in these proteins are deleterious. To test this hypothesis, we investigated the distributions of protein disorder content, i.e., the fraction of disordered regions in a protein [49], across 1,912 protein-coding genes intolerant to heterozygous loss-of-function mutations (pLI score ≥ 0.9). We split the 1,912 genes into two equal-size groups based on their UNEECON-G scores, and defined the 956 genes with higher UNEECON-G scores as the gene set intolerant to both missense and loss-of-function mutations.…”
Section: Missense Constraints and Loss-of-function Constraints Are Wementioning
confidence: 99%